2018
DOI: 10.1073/pnas.1807245115
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala lesions eliminate viewing preferences for faces in rhesus monkeys

Abstract: In free-viewing experiments, primates orient preferentially toward faces and face-like stimuli. To investigate the neural basis of this behavior, we measured the spontaneous viewing preferences of monkeys with selective bilateral amygdala lesions. The results revealed that when faces and nonface objects were presented simultaneously, monkeys with amygdala lesions had no viewing preference for either conspecific faces or illusory facial features in everyday objects. Instead of directing eye movements toward soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 52 publications
6
58
0
Order By: Relevance
“…6). These results are consistent with the findings of previous studies (Emery, 2000;Mosher et al, 2014;Dal Monte et al, 2015;Forcelli et al, 2016;Minxha et al, 2017;Taubert et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…6). These results are consistent with the findings of previous studies (Emery, 2000;Mosher et al, 2014;Dal Monte et al, 2015;Forcelli et al, 2016;Minxha et al, 2017;Taubert et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…While the amygdala is known to mediate threat detection and passive fear responses, it remains unclear if this structure also contributes to controlling eye movements. Some studies have shown that amygdala lesions alter gaze patterns, especially for face images (Dal Monte et al, 2015;Taubert et al, 2018). Other studies have shown that amygdala neurons are spatially selective and encode information about both the location and the motivational significance of visual cues (Peck and Salzman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that human faces and illusory faces are readily decoded from each other in both fMRI and MEG is also indicative of differences in their representation. Overall, this difference is consistent with the interpretation of illusory faces as a quickly resolved error of a broadly tuned face-detection system 2,3 . Thus although illusory faces elicit a face-like response, they are not represented in the same way as human faces within the visual system.…”
Section: Discussionsupporting
confidence: 84%
“…A rapid subcortical route for face detection has been proposed based on multiple lines of evidence 28 , involving the superior colliculus, pulvinar, and amygdala. The amygdala has been implicated in orienting toward faces in primates, and amygdala lesions impair this tendency for both real and illusory faces 3 . Along with the timescale of the early confusion we observe between real and illusory face processing, this is suggestive of a possible role for the amygdala in falsely detecting faces in everyday objects.…”
Section: Discussionmentioning
confidence: 99%
“…The eyes of others became a more prominent signal along evolution due to anatomical changes in facial morphology that have forced a shift in salience from the shape of the face to the eyes 2 . The importance of the amygdala in processing of eye-gaze was shown in humans and in macaques 13,18,23,[47][48][49][50][51] . Here, we recorded neural activity in the amygdala and the ACC during live interactions in a modified version of the human intruder test (HIT) that includes also a conditioning paradigm.…”
mentioning
confidence: 99%